Pottery Industry and Value Chain Model: A Conceptual Study (International Journal of Multidisciplinary Research and Explorer, 2025)
Decrease market demand, low profitability, labour turnover and unsound financial situation is what characterise pottery industry in today`s scenario. Value chain model primary activities of inbound logistic, operations, outbound logistic, marketing & sales and service activities are needed systematically to be executed with support activities of procurement; human resource management, technological development and infrastructure, in case of pottery industry, these activities to be performed systematically require organising of artisans, government assistance and social as well as psychological motivation. Thus, a new framework is framed keeping these points in view. The study using literatures of various authors attempts to study pottery industry using value chain model and suggest a viable solution in the form of new framework to improve the situation of pottery industry.